Performance Federalism and Local Democracy: Theory and Evidence from School Tax Referenda. Issue 2 (6th May 2015) - Kogan, Vladimir; Lavertu, Stéphane; Peskowitz, Zachary
Abstract : Federal governments are increasingly employing empirical measures of lower‐level government performance to ensure that provincial and local jurisdictions pursue national policy goals. We call this burgeoning phenomenon " performance federalism " and argue that it can distort democratic accountability in lower‐level elections. We estimate the impact of a widely publicized federal indicator of local school district performance—one that we show does not allow voters to draw valid inferences about the quality of local educational institutions—on voter support for school tax levies in a U.S. state uniquely appropriate for this analysis. The results indicate that a signal of poor district performance increases the probability of levy failure, a substantively large and robust effect that disproportionately affects impoverished communities. The analysis employs a number of identification strategies and tests for multiple behavioral mechanisms to support the causal interpretation of these findings.